In Vivo Assessment of the Nutritional Efficacy of Encapsulated Squalene in Male Wistar Rats - Kumar, Lekshmi R G; Tejpal, C S; Anas, K K; Vishnu, K V; Ganesan, B; Anandan, R; Mathew, Suseela (Fishery Technology, 2025)
Squalene, a triterpenoid compound, possesses potent bioactivities by virtue of its high degree of unsaturation. In the present study, stable squalene microparticles prepared via spray drying-mediated encapsulation were subjected to a detailed nutritional assessment in male Wistar albino rats. Experimental animals were divided into four groups– I, II, III and IV, and were fed encapsulated squalene at the rate of 0, 150, 300 and 450 mg/kg body weight, respectively. The treatment groups fed with encapsulated squalene showed improved weight gain percentage and specific growth rate. Squalene supplementation could also lower cholesterol, low density lipoprotein and very low-density lipoprotein levels, suggesting its cardioprotective property. The findings of the study indicate thatencapsulated squalene powder can be effectively used as a dietary supplement for improved growth performance along with lipid-lowering attributes.